Pregnancy in patients with immune-mediated inflammatory diseases - Verónica Sánchez-García; Isabel Belinchón-Romero (Publicaciones Permanyer, 2022)
A large percentage of patients with immune-mediated inflammatory diseases (IMIDs) are women of childbearing age. Pregnancy is a complex physiological scenario and causes significant endocrine and immunological changes. Pregnancy can trigger a worsening of IMIDs and, bidirectionally, disease flares are associated with worse pregnancy outcomes. This highlights the importance of achieving adequate control of IMIDs before conception and during pregnancy. When choosing pharmacological therapy in pregnant women with IMIDs, it is important to be aware of all available options and their potential impact on the mother and fetus. The aim of this review is to highlight the influence of pregnancy on the clinical evolution and prognosis of the most common cutaneous, rheumatological, and gastroenterological IMIDs. In addition, we provide an updated review of the different systemic and topical therapies used for the treatment of common dermatoses (such as atopic dermatitis, psoriasis, and hidradenitis suppurativa) and their safety profile during pregnancy and lactation.